Impacts of climate change on biodiversity and ecosystems in Bavaria: a sectoral analysis - Sven Rubanschi; Anne Lewerentz; Andreas Krause; Jana Blechschmidt; Stefan Fallert; Elizabeth Gosling; Konstantin Gregor; Isabelle Jarisch; Christian Stetter; Maximilian Brönner; Florian Hartig; Markus Hoffmann; et al. (Regional Environmental Change, 2026)
Climate change is expected to create a range of impacts on biodiversity, land use, and economic activities, but those sector impacts are rarely analysed together. Here, we assess how climate change and socioeconomic narratives will affect land use and biodiversity in the state of Bavaria, Germany. We apply a multi-sectoral modelling approach with two climate projections (RCP 2.6 and 8.5) downscaled from three different climate models in combination with three land-use scenarios: biodiversity protection, climate change mitigation, and climate change adaptation. We evaluate changes in different sectors such as forestry and agriculture, considering impacts on carbon storage, terrestrial and aquatic biodiversity, and the adaptation of agricultural practices. In our simulations, biodiversity declined sharply under the higher emission scenario, highlighting climate change as a major threat to biodiversity in Bavaria. Prioritising biodiversity through forest conversion and expanding pasture reduced species decline and enhanced carbon storage more effectively than pure climate-focused mitigation. Climate change intensity had minimal impacts on land-use patterns (e.g. allocation of forest types), but it significantly changed farmers’ preferences, increasing their inclination toward more conservative land management practices, i.e. favouring the status quo. We conclude from our findings that policymakers should strategically prioritise biodiversity protection alongside targeted forest-management practices to simultaneously enhance ecosystem health, biodiversity, and carbon storage. Intensified agricultural and land management, on the other hand, should be approached cautiously to avoid biodiversity loss.

Confronting sustainable intensification with uncertainty and extreme values on smallholder tropical farms - Thomas Knoke; Elizabeth Gosling; Esther Reith; Andres Gerique; Perdita Pohle; Liz Valle Carrión; Wilman Santiago Ochoa Moreno; Luz Maria Castro; Baltazar Calvas; Patrick Hildebrandt; Martin Döllerer; Félix Bastit; et al. (Sustainability Science, 2022)
Sustainable intensification of agricultural lands might reconcile the conservation of tropical forest with food production, but in-depth assessments considering uncertainty and extreme values are missing. Uncertainty prohibits mapping probabilities to potential future states or ranking these states in terms of their likelihood. This in turn hampers the assessment of possible decision outcomes. Here, we use simulations to investigate how uncertainty may influence the social acceptability of alternative land-use strategies to halt tropical deforestation (including sustainable intensification), based on indicators representing farmer satisfaction. The results show how extreme values (worst values) for indicators of farmer satisfaction may undermine the adoption of sustainable intensification. We demonstrate that a pure forest conservation strategy leads to lower food production, but outperforms a sustainable intensification strategy that maintains food security. Pure forest conservation performed better, i.e., could secure higher farmer satisfaction, than sustainable intensification across a range of indicator groups. This suggests strong barriers to achieving sustainable intensification. Using agricultural subsidies breaks the dominance of pure forest conservation by enhancing the economic returns of sustainable intensification. We discuss the importance of access to labor and farmers’ preferences for the use of already cleared lands, which achieved the worst values under sustainable intensification and conclude that any assessment of land-use strategies requires careful consideration of uncertainty and extreme values.

Accounting for multiple ecosystem services in a simulation of land‐use decisions: Does it reduce tropical deforestation? - Thomas Knoke; Carola Paul; Anja Rammig; Elizabeth Gosling; Patrick Hildebrandt; Fabian Härtl; Thorsten Peters; Michael Richter; Karl‐Heinz Diertl; Luz Maria Castro; Baltazar Calvas; Santiago Ochoa; et al. (Global Change Biology, 2020)
Conversion of tropical forests is among the primary causes of global environmental change. The loss of their important environmental services has prompted calls to integrate ecosystem services (ES) in addition to socio‐economic objectives in decision‐making. To test the effect of accounting for both ES and socio‐economic objectives in land‐use decisions, we develop a new dynamic approach to model deforestation scenarios for tropical mountain forests. We integrate multi‐objective optimization of land allocation with an innovative approach to consider uncertainty spaces for each objective. These uncertainty spaces account for potential variability among decision‐makers, who may have different expectations about the future. When optimizing only socio‐economic objectives, the model continues the past trend in deforestation (1975–2015) in the projected land‐use allocation (2015–2070). Based on indicators for biomass production, carbon storage, climate and water regulation, and soil quality, we show that considering multiple ES in addition to the socio‐economic objectives has heterogeneous effects on land‐use allocation. It saves some natural forest if the natural forest share is below 38%, and can stop deforestation once the natural forest share drops below 10%. For landscapes with high shares of forest (38%–80% in our study), accounting for multiple ES under high uncertainty of their indicators may, however, accelerate deforestation. For such multifunctional landscapes, two main effects prevail: (a) accelerated expansion of diversified non‐natural areas to elevate the levels of the indicators and (b) increased landscape diversification to maintain multiple ES, reducing the proportion of natural forest. Only when accounting for vascular plant species richness as an explicit objective in the optimization, deforestation was consistently reduced. Aiming for multifunctional landscapes may therefore conflict with the aim of reducing deforestation, which we can quantify here for the first time. Our findings are relevant for identifying types of landscapes where this conflict may arise and to better align respective policies.